Analisis Kemampuan Literasi Sains pada Siswa Sekolah Dasar Ditinjau dari Aspek Konten, Proses, dan Konteks Sains - Siti Hanifa Ari Utami*; Putut Marwoto; Woro Sumarni (Universitas Syiah Kuala, 2022)
The low level of scientific literacy is due to the lack of success of students in completing the types of scientific literacy with characteristics. This research aims to determine the literacy achievement of elementary school students in terms of content, process, and science context aspects. The sampling technique used is purposive sampling, where the sampling criteria are based on suggestions from the class teacher and the characteristics of the students themselves. The teacher suggested that the class that had received the material to be tested were class VI, which consisted of 31 students from 16 female students and 15 male students. The research instrument used was a scientific literacy test in the form of 10 multiple-choice questions on the human digestive system material which included aspects of the content, process, and context of scientific literacy. Data were analyzed by descriptive percentage formula. The results showed that the average scientific literacy ability as a whole obtained a percentage value of 51.09% in the low category. In the content aspect, it obtained a percentage value of 49.73% with the low achievement category. The process aspect obtained a percentage value of 44.43% in the low category. Meanwhile, the context aspect shows the highest gain among other aspects of scientific literacy ability, which is 59.13% in the medium category. Conclusion, students' literacy skills are still low, so teachers must pay more attention to improving students' scientific literacy skills through a contextual learning process by connecting science and the application of science in students' daily lives